Functional Regions of the Medial Patellofemoral Ligament - Ji, Gang; Sun, Yifei; Lu, Jiangfeng; Niu, Yingzhen; Wang, Fei (The Journal of Knee Surgery, 2019)
The purpose of this study was to explore the anatomy and discuss functional regions of the medial patellofemoral ligament (MPFL). Twelve fresh-frozen knees specimens were dissected. All medial surfaces of knees were intact and did not have indication of injury. General feature of the MPFL were observed. All anatomical landmarks were carefully identified and marked. The length of the two functional regions were conducted and recorded. All data were obtained, described, and analyzed in the form of mean ± standard deviation. The MPFL was found in all specimens we dissected. Closed to the patellar insertion, it adheres to the deep surface of the vastus medialis obliquus (VMO). Due to the VMO, the MPFL is divided into two functional regions: overlap region and nonoverlap region. Anatomically, the overlap region and nonoverlap region of 25.43 ± 2.0 and 44.85 ± 3.04 mm, the width of VMO insertion is 13.94 ± 2.03 mm, and the width of patellar insertion is 22.91 ± 3.46 mm. We divide the MPFL into two anatomical functional regions, demarcated by the meshing points of fibers between the MPFL and VMO: overlap region and nonoverlap region. This finding provides the theoretical foundation for the treatment of the MPFL injury and shed lights on the future researches.
Keywords: MPFL; dissection; functional regions; treatment